2015
DOI: 10.1016/j.ccell.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of the Human Immunoglobulin G2 Hinge Imparts Superagonistic Properties to Immunostimulatory Anticancer Antibodies

Abstract: SummaryMonoclonal antibody (mAb) drugs that stimulate antitumor immunity are transforming cancer treatment but require optimization for maximum clinical impact. Here, we show that, unlike other immunoglobulin isotypes, human IgG2 (h2) imparts FcγR-independent agonistic activity to immune-stimulatory mAbs such as anti-CD40, -4-1BB, and -CD28. Activity is provided by a subfraction of h2, h2B, that is structurally constrained due its unique arrangement of hinge region disulfide bonds. Agonistic activity can be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
205
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(216 citation statements)
references
References 59 publications
6
205
3
2
Order By: Relevance
“…ChiLob 7/4, a CD40 mAb that has recently completed a phase 1 clinical trial, 66 is agonistic in human CD40 transgenic mice as IgG2 in the absence of FcgR expression and even as a F(ab9) 2 fragment. 60 FcgRindependent activity has also been demonstrated for another IgG2 CD40 mAb in a clinical trial: CP870-893. 67 The key to IgG2 agonistic activity lies in the unique configuration of its hinge region, 60 which can adopt alternative conformations through disulphide rearrangement.…”
Section: Fcgr-independent Effectsmentioning
confidence: 96%
See 3 more Smart Citations
“…ChiLob 7/4, a CD40 mAb that has recently completed a phase 1 clinical trial, 66 is agonistic in human CD40 transgenic mice as IgG2 in the absence of FcgR expression and even as a F(ab9) 2 fragment. 60 FcgRindependent activity has also been demonstrated for another IgG2 CD40 mAb in a clinical trial: CP870-893. 67 The key to IgG2 agonistic activity lies in the unique configuration of its hinge region, 60 which can adopt alternative conformations through disulphide rearrangement.…”
Section: Fcgr-independent Effectsmentioning
confidence: 96%
“…60 FcgRindependent activity has also been demonstrated for another IgG2 CD40 mAb in a clinical trial: CP870-893. 67 The key to IgG2 agonistic activity lies in the unique configuration of its hinge region, 60 which can adopt alternative conformations through disulphide rearrangement. [68][69][70] IgG2 is believed to be synthesized with all 4 heavy chain (HC) hinge cysteines involved in parallel inter-HC disulphide bonds, a conformation designated as IgG2(A).…”
Section: Fcgr-independent Effectsmentioning
confidence: 96%
See 2 more Smart Citations
“…The molecular mechanisms required for making good agonistic antibodies were dissected in depth by Dr. Glennie (University of Southampton School of Medicine, Southampton, United Kingdom). He showed that agonistic antibodies targeting the family of TNFR need crosslinking by FcgRIIB, but the antibody can also be engineered to obtain superagonistic antibodies independent of cross-linking, tampering with the structure of the antibody to confer a more rigid conformation of the hinge (19).…”
Section: New Avenues and Adventures In Cancer Immunotherapymentioning
confidence: 99%